PENATALAKSANAAN AWAM TERAMPIL KHUSUS PADA REMAJA - M. Lutfi (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2019)
The concept of handling emergency patients is "time saving is life and limb saving". Patients are generally found by those closest to them who can be categorized as lay people (health cadres, communities, families, teachers, scouts, security guards, police, firefighters, etc.). When an accident / trauma occurs, the sufferer begins “the golden hour”. According to WHO (World Health Organization), it is estimated that from 2005-2010 there were 850 deaths per 100,000 population that occurred each year. Emergency case visit rates vary in the number of cases at various health centers in different countries. Based on an observation by Pleh Wier, there were more than 120 million cases of emergency in 2009 in the United States. Based on a survey through interviews with a special layman at SMK Kesehatan Al-As'Yari Kec. Kawanyar Kab. In Bangkalan, information was obtained that many students of the Al-As'Yari Health Vocational School still did not know about first aid in handling emergency patients. The participants of the activity were 20 students of the Al-As'Yari Health Vocational School who took part in the emergency first aid training. During the special lay activities, he was very enthusiastic about the material presented. There is an increase in specific lay knowledge before and after being given training. Before the training, there was only 25% category and 75% less category. After being given counseling, it increased to be in the good category, namely by 75%. The results of special training for the layman were also skilled at performing basic life support for bandaging and seeding. The special layman also understands the concept of first aid that should be given to patients with an emergency.